(untitled) (Annals of Medical Research, 2023)
Aim: Our study aimed to find the relationship between MPV (Mean Platelet Volume) levels, a marker of inflammation, and platelet counts between simple and complex febrile seizures. Materials and Methods: In this retrospective comparative study, we analyzed the records of 283 children between the ages of 6 months and 6 years who were diagnosed with simple and complex febrile seizures (BFN/CFN) in the Pediatric Neurology Clinic of XXX University, Faculty of Medicine between January 2021 and December 2022. Results: The mean age and gender characteristics of the patients were similar in both groups. The MPV of the CFN group (69 patients) (6.53±0.39fl) was lower than that of the BFN group (214 patients) (7.81±0.43fl) and this difference was statistically significant (p<0.01). The platelet count of the CFN group (257.42×103±126.01×103) was higher than that of the BFN group (191.23×103±68.29×103) and the difference was statistically significant (p<0.01). Conclusion: There was a significant difference between BFN and CFN groups in terms of both MPV values and platelet counts. This study suggests that detailed and comprehensive studies on MPV and platelet counts may guide cases where clinical findings are suspicious and the distinction between BFN and CFN cannot be clearly differentiated.